La interminable huelga de los mineros mexicanos de Cananea :¿El final de un régimen laboral ? - Juan Luis Sariego (Les Cahiers ALHIM)
The Mexican Mining industry lives in the last two decades a time of unprecedented growth. This process is the result of several factors : the exorbitant increase in the prices of metals, the globalization of the industry, the liberalization of the mining law, tax deregulation, and openness to foreign capital and privatization of the mines. In this context, we analyze the meaning of the long strike by copper miners in Cananea, Sonora held since June 2012. This movement expresses the end of a long period of corporate relations between the state and the working class and is a benchmark of the new paradigm of labor policy in Mexico.